RAGAM PENDAPATAN RUMAH TANGGA DAN FAKTOR YANG MEMPENGARUHI: STUDI KASUS DI DESA-DESA SEKITAR KAWASAN TAMAN NASIONAL KERINCI SEBLAT (TNKS) KABUPATEN LEBONG PROVINSI BENGKULU - Nola Windirah; Ketut Sukiyono; Septri Widiono (Jurnal Agrisep)
This research is aimed at exploring level of household income diversity based on agricultural land typology and examining factors that affect household income diversity in villages around TNKS, Regency of Lebong, Province of Bengkulu. This research uses secondary and primary data. Respondents of this research were determined randomly as much as 400 respondents in 20 villages. Analysis method diversity used are F test and t test to infestigate the differences of household income and multiple linear regression to examining the factors that affect the diversity of household income by applying and developing Minot. et al (2006) model. Result of this research showed that there are differences of household income diversity agricultural land typology, eventhing the existing are not significant among typologies and the factors that affect the household income diversity are education of the head of the family, agricultural land area, and amount of main income household.